Exploiting targeted nanomedicine for surveillance, diagnosis, and treatment of hepatocellular carcinoma - Tingting Liu; Li Liu; Li Li; Jing Cai (Materials Today Bio, 2023)
Hepatocellular carcinoma (HCC) is one of the cancers that has the highest morbidity and mortality rates. In clinical practice, there are still many limitations in surveilling, diagnosing, and treating HCC, such as the poor detection of early HCC, the frequent post-surgery recurrence, the low local tumor control rate, the therapy resistance and side effects. Therefore, improved, or innovative modalities are urgently required for early diagnosis as well as refined and effective management. In recent years, nanotechnology research in the field of HCC has received great attention, with various aspects of diagnosis and treatment including biomarkers, ultrasound, diagnostic imaging, intraoperative imaging, ablation, transarterial chemoembolization, radiotherapy, and systemic therapy. Different from previous reviews that discussed from the perspective of nanoparticles’ structure, design and function, this review systematically summarizes the methods and limitations of diagnosing and treating HCC in clinical guidelines and practices, as well as nanomedicine applications. Nanomedicine can overcome the limitations to improve diagnosis accuracy and therapeutic effect via enhancement of targeting, biocompatibility, bioavailability, controlled releasing, and combination of different clinical treatment modalities. Through an in-depth understanding of the logic of nanotechnology to conquer clinical limitations, the main research directions of nanotechnology in HCC are sorted out in this review. It is anticipated that nanomedicine will play a significant role in the future clinical practices of HCC.